Diagnostic Review of Consumer Protection and Financial Literacy : Vietnam, Volume 2 - World Bank Group (Washington, DC: World Bank, 2017)
In 2011, only 21.4 percent of Vietnamese adults had an account at a formal financial institution, and only 36.9 percent of all borrowers used a formal lender - both indicators are well below the regional averages in the East Asia and Pacific. The formal financial sector in Vietnam is dominated by banks; however, retail lending is still rather underdeveloped due to often flawed lending practices and low levels of financial literacy among the population. Vietnamese authorities and the civil society have demonstrated a deep commitment to financial consumer protection by continuous dialogue and persistent legislative activities, and yet, much still needs to be achieved. The legal and regulatory framework for consumer protection in the financial sector, and related supervisory arrangements, are at a nascent stage of development. This World Bank’s diagnostic review was conducted in response to a request from the State Bank of the Socialist Republic of Vietnam. The banking, non-bank credit institutions, securities, insurance, and credit reporting sectors were considered as well as financial literacy strategies and programs. The review was conducted by reference to the World Bank`s good practices for financial consumer protection and provides a detailed assessment of the institutional, legal, and regulatory framework for financial consumer protection. Volume I of the review summarizes the key findings and recommendations and volume II provides a detailed comparison with the good practices.